2013
DOI: 10.1186/1471-230x-13-47
|View full text |Cite
|
Sign up to set email alerts
|

Medical and surgical treatment of haemorrhoids and anal fissure in Crohn’s disease: a critical appraisal

Abstract: BackgroundThe principle to avoid surgery for haemorrhoids and/or anal fissure in Crohn’s disease (CD) patients is still currently valid despite advances in medical and surgical treatments. In this study we report our prospectively recorded data on medical and surgical treatment of haemorrhoids and anal fissures in CD patients over a period of 8 years.MethodsClinical data of patients affected by perianal disease were routinely and prospectively inserted in a database between October 2003 and October 2011 at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
45
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 28 publications
(36 reference statements)
0
45
0
2
Order By: Relevance
“…In addition, surgical intervention on perianal lesions may increase the risk of fistula development. 15,21 Other than abscesses, most perianal lesions of Crohn's disease respond to medical therapy without surgery. 22 This finding suggests that surgery for Crohn's disease-related perianal lesions other than abscesses may not be beneficial and could result in worse outcomes than medical therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, surgical intervention on perianal lesions may increase the risk of fistula development. 15,21 Other than abscesses, most perianal lesions of Crohn's disease respond to medical therapy without surgery. 22 This finding suggests that surgery for Crohn's disease-related perianal lesions other than abscesses may not be beneficial and could result in worse outcomes than medical therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Such cases are rarely reported. [15][16][17] The present case series describes patients who underwent surgery for perianal lesions not previously recognized to be Crohn's disease related but subsequently were found to be associated with perianal fistulizing Crohn's disease.…”
mentioning
confidence: 99%
“…In a series of 12 patients half required proctectomy following complications of haemorrhoidectomy [15]. Vignal et al and Keighley and Allan showed similar rate of severe complications in CD [16,17], but other authors have reported haemorrhoidectomy to be safe in CD with a low risk of complications [4,7,[18][19][20][21]. In patients with UC there is less information.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies were identified with a low complication rate [1,15,22]. Few authors have reported the duration of the interval from haemorrhoidectomy to complications leading to major surgery [4,16,19]. It is unclear if the complication should be attributed to the disease or to the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Three patients complained of a not healed wound at the site of LIS. LIS was performed in unknown CD only in six out of 48 patients (12 %) [1]. The interval between surgery and occurrence of a complication was reported only in three studies and ranged from 4 months to 9 years (mean 16 months) [2][3][4].…”
mentioning
confidence: 99%